B‐type natriuretic peptide predicts stroke of presumable cardioembolic origin in addition to coronary artery calcification. (24th March 2014) - Kara, K.; Gronewold, J.; Neumann, T.; Mahabadi, A. A.; Weimar, C.; Lehmann, N.; Berger, K.; Kälsch, H. I. M.; Bauer, M.; Broecker‐Preuss, M.; Möhlenkamp, S.; Moebus, S.; et al.
<x xml:space="preserve">Abstract</x> Background and purpose B‐type natriuretric peptide (BNP) is a marker of cardiac dysfunction that is released from myocytes in response to ventricular wall stress. Previous studies suggested that BNP predicts stroke events in addition to classical risk factors. It was suggested that the BNP‐associated risk results from coronary atherosclerosis or atrial fibrillation. Methods Three thousand six hundred and seventy five subjects from the population‐based Heinz Nixdorf Recall study (45–75 years; 47.6% men) without previous stroke, coronary heart disease, myocardial infarcts, open cardiac valve surgery, pacemakers and defibrillators were followed up over 110.1 ± 23.1 months. Cox proportional hazards regressions were used to examine BNP as a stroke predictor in addition to vascular risk factors (age, gender, systolic blood pressure, low‐density lipoprotein, high‐density lipoprotein, diabetes, smoking), renal insufficiency, atrial fibrillation/known heart failure and coronary artery calcification. Results Eighty‐nine incident strokes occurred (80 ischaemic, 9 hemorrhagic). Subjects suffering stroke had significantly higher BNP values at baseline than the remaining subjects [26.3 (Q1; Q3 = 12.9; 51.0) vs. 17.4 (9.4; 31.4); P < 0.001]. In a multivariable regression, log10BNP was an independent stroke predictor [hazard ratio 1.96, 95% confidence interval (CI) 1.13–3.41; P = 0.017] in addition to age (1.24 per 5 years, CI 1.04–1.49; P = 0.016), systolic blood pressure (1.25 per 10 mmHg, CI 1.14–1.38; P < 0.001), smoking (2.05, CI 1.24–3.39; P = 0.005), atrial fibrillation/heart failure (2.25, CI 1.05–4.83; P = 0.037) and computed‐tomography‐based log10(coronary artery calcification + 1) (1.47, CI 1.15–1.88; P = 0.002). Log10BNP predicted stroke in men but not women, both in subjects ≤65 and >65 years. In subsequent analyses, BNP discriminated the incidence of cardioembolic stroke (P for trend = 0.001), but not stroke of macroangiopathic (P = 0.555), microangiopathic (P = 0.809) or unknown (P = 0.367) origin. Conclusions BNP predicts presumable cardioembolic stroke independent of coronary calcification.